Dynamic modeling of flow boiling within plate heat exchangers for heat pump and refrigeration applications - Böse, Lennart; Opferkuch, Frank; Becker, J.; Wensing, Michael; et al. (IGSHPA Research Track, 2018)
Brazed Plate Heat Exchangers (BPHEs) are increasingly used as evaporators for refrigeration and heat pump applications. Detailed understanding of the underlying heat transfer phenomena is required for their effective design and use. The number of correlations which are suitable for modeling the dynamics of flow boiling within BPHEs is rather low compared to other evaporator types. In this paper some correlations that involve integral values of steam quality are evaluated for different sets of experimental data from literature. Modifications to the correlations are presented, which allow to predict the quasi-local heat transfer coefficient in each refrigerant cell. The cells equal finite volumes that are composed to a dynamic model of a BPHE acting as evaporator. Heat transfer coefficient and heat flow rate from simulation results are compared to those calculated from existing experimental data based on the same boundary conditions. The fine-tuned evaporator model is finally used to demonstrate effects of sudden load changes for the Evaporator performance. <br

Steam Storage Rankine Cycle for Unutilized Applications in Distributed High-Temperature Waste Heat Recovery - Raab, Florian; Böse, Lennart; Klein, Harald; Opferkuch, Frank (Energies, 2024)
In the light of increasingly valuable resources and a trend towards more efficient processes pushed by climate change, distributed Waste Heat Recovery (WHR) is an important element in the transformation of the energy supply. In recent years, however, WHR systems have often been optimized and implemented for steady-state applications. In this paper, dynamic system modeling and a Steam Rankine Cycle (SRC) pilot plant with 40 kWel are used to investigate applications unutilized thus far for the conversion of high-temperature waste heat into electricity using a shell boiler with 1.27 m3 of liquid water for short-term energy storage. In addition to experimental investigations of the storage system as an Uninterruptible Power Supply (UPS) and the input and output of +/−100% electrical power peaks for grid-assistive operation, a control concept for the use of volatile waste heat is developed from a model-based controller design up to a Model Predictive Control (MPC) with the help of a dynamic system simulation. Based on the validated model and experimental measurement data, outlooks for concrete applications with higher storage capacity and power are provided.
CRIS-Team Scopus Importer:2024-03-01
Keywords: dynamic model; experimental investigation; Steam Rankine Cycle; steam storage; waste heat recovery